Advising Nixon : The White House Memos of Patrick J. Buchanan - Buchanan, Patrick J. (Patrick Joseph), 1938- (Book collections on Project MUSE., 2019)
"Presidential documents provide a unique perspective into the decision making and thought processes of some of the most powerful figures in American government, and the memos of Patrick J. Buchanan, advisor to President Richard Nixon are no exception. Buchanan regularly wrote numerous memos each day, many of which are long and detailed. In them, he gave Nixon advice on communication strategies, press relations, policy positions, and how to navigate the political environment. Throughout his political career, Buchanan has been known for fiery rhetoric that does not mince words regarding his traditional conservative views. The memos he crafted during the Nixon years were written in the same style and tone, either counter-punching against views from other White House advisors Buchanan viewed as too moderate or providing Nixon with a take-no-prisoners approach to every political battle that presented itself. This book offers a close examination of Buchanan's role in the Nixon White House, previously untouched as a topic of a book-length scholarly study and using White House memos to provide a behind-the-scenes analysis. Nixon first hired Buchanan to help lay the groundwork for the 1968 presidential campaign, and subsequently he became one of Nixon's closest advisors. While many books have been written about the Nixon years, this book gives readers direct access to the memos themselves. Lori Cox Han has sifted through the Nixon Library archives and organized more than 400 memos that best exemplify Buchanan's unique perspectives on nearly all the relevant political issues during his time in the Nixon administration. Introduced and annotated by Cox, Advising Nixon gives us a behind-the-scenes look into one of the most consequential presidencies in our nation's history"--